Optimized excystation protocol for ruminant Eimeria bovis- and Eimeria arloingi-sporulated oocysts and first 3D holotomographic microscopy analysis of differing sporozoite egress. (June 2020) - López-Osorio, Sara; Silva, Liliana M.R.; Chaparro-Gutierréz, Jenny J.; Velásquez, Zahady D.; Taubert, Anja; Hermosilla, Carlos
Abstract: Successful excystation of sporulated Eimeria spp. oocysts is an important step to acquire large numbers of viable sporozoites for molecular, biochemical, immunological and in vitro experiments for detailed studies on complex host cell-parasite interactions. An improved method for excystation of sporulated oocysts and collection of infective E. bovis- and E. arloingi- sporozoites is here described. Eimeria spp. oocysts were treated for at least 20 h with sterile 0.02 M L -cysteine HCl/0.2 M NaHCO3 solution at 37 °C in 100% CO2 atmosphere. The last oocyst treatment was performed with a 0.4% trypsin 8% sterile bovine bile excystation solution, which disrupted oocyst walls with consequent activation of sporozoites within oocyst circumplasm, thereby releasing up to 90% of sporozoites in approximately 2 h of incubation (37 °C) with a 1:3 (oocysts:sporozoites) ratio. Free-released sporozoites were filtered in order to remove rests of oocysts, sporocysts and non-sporulated oocysts. Furthermore, live cell imaging 3D holotomographic microscopy (Nanolive®) analysis allowed visualization of differing sporozoite egress strategies. Sporozoites of both species were up to 99% viable, highly motile, capable of active host cell invasion and further development into trophozoite- as well as macroment-development in primary bovine umbilical vein endothelial cells (BUVEC). Sporozoites obtained by this new excystation protocol were cleaner at the time point of exposure of BUVEC monolayers and thus benefiting from the non-activation status of these highly immunocompetent cells through debris. Alongside, this protocol improved former described methods by being is less expensive, faster, accessible for all labs with minimum equipment, and without requirement of neither expensive buffer solutions nor sophisticated instruments such as ultracentrifuges. Graphical abstract: Unlabelled Image Highlights: Present study provides an improved excystation protocol to obtain viable sporozoites from ruminants Eimeria spp. The method is cheaper, faster, and accessible for all labs with minimum equipment. We achieved a higher excystation rate, which reduced the initial number of oocysts per sporozoites needed.